2001
DOI: 10.1016/s0735-1097(01)01510-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence supporting abnormalities in nitric oxide synthase function induced by nitroglycerin in humans

Abstract: The response to Ach confirms the hypothesis that continuous GTN causes endothelial dysfunction. The responses to L-NMMA suggest that GTN therapy causes abnormalities in nitric oxide synthase (NOS) function; the vasodilation observed at the lowest infused concentration of L-NMMA in the GTN group also suggests that continuous GTN therapy is associated with a NOS-mediated production of a vasoconstrictor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
92
1
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 26 publications
4
92
1
2
Order By: Relevance
“…8 -12 Furthermore, continued use of GTN is associated with endothelial dysfunction, a predictor of adverse cardiac events. 11,13,14 Thus, the molecular basis of neither GTN bioactivation nor tolerance is well understood.…”
mentioning
confidence: 99%
“…8 -12 Furthermore, continued use of GTN is associated with endothelial dysfunction, a predictor of adverse cardiac events. 11,13,14 Thus, the molecular basis of neither GTN bioactivation nor tolerance is well understood.…”
mentioning
confidence: 99%
“…4 In addition, Gori et al have shown that continuous NTG treatment induces significant changes in the function of the endothelium in humans. 18 However, in this study, we could not evaluate the extent to which exogenous NO, such as ambient environment, food, and water, affected our results. Further studies will be needed on this subject.…”
Section: Discussionmentioning
confidence: 84%
“…Increased vascular peroxynitrite formation might affect the proper function of eNOS and thus induce the impairment of bioavailability of NO. As pointed out by Gori et al, 2 peroxynitrite is a strong stimulus for the oxidation of the eNOS cofactor BH4 to dihydrobiopterin. The resulting intracellular BH4 deficiency might switch eNOS from a NO to a superoxide-producing enzyme, which may further increase oxidative stress in vascular tissue in a positive feedback fashion.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations